The level of residue of pesticides in vegetables by GC-MS, health risk and the negligence in implementation of policies, India - Khan, Azra; Srivastava, J. P.; Bose, Dipak Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Over the past years there has been an increase in the use of pesticides in vegetable farming developing countries. This study describes over spraying pesticide use among small-scale farmers in Jasra block of Allahabad district of Uttar Pradesh. Methods: The purpose of this study was proposed to determine the pesticide residual level in 120 vegetable samples like brinjal, lady finger, tomato, chili, cabbage analysed by (GC-MS) gas chromatography mass spectrophotometry technique. Assessing the health risk due to the daily consumption of contaminated vegetables Jasra block of Allahabad district. Results: Samples were contaminated with organophosphorus group namely chlorpyriphos in bringal 1.215 mg/kg, and less carbamate (carbaryl) from 0.025 mg/kg, ladyfinger with the concentration of chlorpyriphos 0.418 mg/kg carbaryl 0.092 with very less residue of dichlorvos 0.005, green chilli with the concentration of chloropyriphos 1.507 mg/kg. Carbaryl 0.033 mg/kg, tomato with the concentration of chlorpyriphos 1.631mg/kg followed by less carbaryl 0.026 mg/kg, malathione, 1.890 mg/kg followed by cabbage with the concentration of chlorphyriphos 1.907 mg/kg. And less carbaryl concentration was recorded 0.064 mg/kg. Conclusions: Five vegetable with pesticides residues, exceeding the maximum residue level (MRL) recommended by FSSAI, FAO/WHO. Farmers over spraying methods leads to acute diseases like respiratory tract infection, extreme weakness, and longer use pesticides exposure leads to chronic diseases like asthma, anxiety, depression, cancer, leukemia, allergies, nausea, vomiting, headache, blur vision, skin itching etc.to minimize the risk of diseases policy making and farmer protection standard and proper handling techniques, trained professionals to improve health safety.